83.8k views
4 votes
Simplify these expression a.-8p + (-9p)+(-2p) b. -3jk+5jk+(-6jk)

User Don Briggs
by
5.4k points

2 Answers

3 votes

Answer:

a. –8p + (–9p) + (–2p)

Combine the coefficients of the like monomials.

[(–8) + (–9) + (–2) = –19]

Answer: –19p

b. –3jk + 5jk + (–6jk)

Combine the coefficients the like of monomials.

[(–3) + 5 + (–6) = –4]

Answer: –4jk

Explanation:

straight from Penn

User Baptiste Arnaud
by
5.3k points
6 votes

Explanation:

Combine like terms

a. -8p + (-9p) + (-2p) = -8p -9p -2p = (-8 - 9 - 2)p = -19p

b. -3jk + 5jk + (-6jk) = -3jk + 5jk - 6jk = (-3 + 5 - 6)jk = -4jk

Terms are called "like terms" if they have the same variable part (the same letters in the same powers). Like terms differ at most coefficient.

User Fawkes
by
5.5k points